Study of Viscous Fluid in the Presence of Transverse Magnetic Field via Spherical and Cylindrical Structure - Ramesh Yadav; Pravin Kumar Srivastava; Santosh Kumar Dixit; Ravindra Pratap Pandey; Navneet Kumar Singh (International Journal of Mathematics And its Applications, 2023)
Many investigators have discussed the study of the MHD flow of viscous fluid through different structures. In this analysis we study, the concept of streamlined flow in the presence of a transverse magnetic field has been introduced. The main objective of the paper is to discuss the viscous fluid, which is past a sphere or circular cylinder in the presence of a clear and porous zone. The Brinkman model is passed down for the discussion of viscous fluid flow in porous media. The matching condition for the flow of viscous fluid is suggested by Williams. It has been chosen for both structures such as sphere and circular cylinder. The solutions to the problems have been procured analytically. MATLAB software is used for the graphical study. The graphs of streamlined flow in spherical as well as circular cylinders have been studied. It is observed that with the increase of the Magnetic field on the inside of the cylinder the drag increases sharply similar effect is also observed in a circular cylinder. It is also observed that the increase of Magnetic field stress increases sharply. A result of this study is compared with the result procured by putting in the Ochoa Tapia and Whitaker matching conditions at the interface.